Le discours des commentaires sur le football des internautes lecteurs de www.lequipe.fr - Napieralski, Andrzej (Studia Romanica Posnaniensia, 2015)
Internet visitors, having found this instrument of global communication, have discovered a new field of verbal battles where they can release their emotions, expressing completely anonymously views. The Internet has changed the image of debate, and of polemic discussion, which earlier was an exchange of replies, and now thanks to forums and “reactions”, a “bath of opinions” has manifest, where everyone can add his two cents. The commentary we would like to present in this work are the reactions of the readers of the website www.lequipe.fr who after each article had the opportunity to express their arguments and their reactions to the article they had read.